Pilot Study of Aprepitant for Prevention of Post-ERCP Pancreatitis in High Risk Patients: A Phase II Randomized, Double-Blind Placebo Controlled Trial - Shah, Tilak Upendra; Liddle, Rodger; Branch, M Stanley; Jowell, Paul; Obando, Jorge; Poleski, Martin (JOP. Journal of the Pancreas, 2012)
Objectives Animal studies have demonstrated a role for substance P binding to neurokinin-1 receptor in the pathogenesis of acute pancreatitis. Our aim was to assess the efficacy of a neurokinin-1 receptor antagonist (aprepitant) at preventing post-ERCP pancreatitis in high risk patients. Design Randomized, double-blind, placebo controlled trial at a single academic medical center. Intervention Patients at high risk for post-ERCP pancreatitis received either placebo or oral aprepitant administered 4 hours prior to ERCP, 80 mg 24 hours after the first dose, and then 80 mg 24 hours after the second dose. Patients Thirty-four patients received aprepitant and 39 patients received placebo. Statistics Fisher’s exact test was used to compare incidence of post-ERCP pancreatitis in the two groups. Results Baseline characteristics were similar between the two groups. Incidence of acute pancreatitis was 7 in the aprepitant group and 7 in the placebo group. Hospitalization within 7 days post-procedure for abdominal pain that did not meet criteria for acute pancreatitis occurred in 6 and 9 patients in the aprepitant and placebo groups respectively (P=0.772). Conclusions Aprepitant did not lower incidence of post-ERCP pancreatitis in this preliminary human study. Larger studies potentially using the recently available intravenous formulation are necessary to conclusively clarify the efficacy of aprepitant in this setting. Image: Duke University School of Medicine. Durham, VA, USA.